Combining chitin biological conduits with small autogenous nerves and platelet‐rich plasma for the repair of sciatic nerve defects in rats - Lu, Chang‐Feng (CNS Neurosci Ther, 2021)
AIMS: Peripheral nerve defects are often difficult to recover from, and there is no optimal repair method. Therefore, it is important to explore new methods of repairing peripheral nerve defects. This study explored the efficacy of nerve grafts constructed from chitin biological conduits combined with small autogenous nerves (SANs) and platelet‐rich plasma (PRP) for repairing 10‐mm sciatic nerve defects in rats. METHODS: To prepare 10‐mm sciatic nerve defects, SANs were first harvested and PRP was extracted. The nerve grafts consisted of chitin biological conduits combined with SAN and PRP, and were used to repair rat sciatic nerve defects. These examinations, including measurements of axon growth efficiency, a gait analysis, electrophysiological tests, counts of regenerated myelinated fibers and observations of their morphology, histological evaluation of the gastrocnemius muscle, retrograde tracing with Fluor‐Gold (FG), and motor endplates (MEPs) distribution analysis, were conducted to evaluate the repair status. RESULTS: Two weeks after nerve transplantation, the rate and number of regenerated axons in the PRP‐SAN group improved compared with those in the PRP, SAN, and Hollow groups. The PRP‐SAN group exhibited better recovery in terms of the sciatic functional index value, composite action potential intensity, myelinated nerve fiber density, myelin sheath thickness, and gastrectomy tissue at 12 weeks after transplantation, compared with the PRP and SAN groups. The results of FG retrograde tracing and MEPs analyses showed that numbers of FG‐positive sensory neurons and motor neurons as well as MEPs distribution density were higher in the PRP‐SAN group than in the PRP or SAN group. CONCLUSIONS: Nerve grafts comprising chitin biological conduits combined with SANs and PRP significantly improved the repair of 10‐mm sciatic nerve defects in rats and may have therapeutic potential for repairing peripheral nerve defects in future applications.